Asymmetric nexus between energy prices, precious metal prices and stock market prices in the Indian context: evidence from a nonlinear ARDL model approach. (2nd May 2022) - Kumar, Suresh; Singh, Gurcharan; Kumar, Ankit
Relationships among energy, metal and stock prices are of huge interest among various stakeholders around the world. This paper investigates the cointegration among stock market prices, energy prices (crude oil, natural gas) and precious metal prices (gold, silver) in the Indian context using daily data from October 2006 to December 2019. We apply nonlinear autoregressive distributed lag (NARDL) testing approach to explore the associations. Finding shows the presence of cointegration among the selected variables in both the short and long-run. Findings of the paper are of practical interest for academicians, policymakers, practitioners, economic agents, and traders who invest in the stock market.